The Zero Lower Bound on nominal interest rates and its impact on monetary policy in the “New Normal” - Bäumler, Daniel Maximilian Günter (2018)
This dissertation aims to illustrate the impact of the Zero Lower Bound (ZLB) on nominal interest rates, based on a deterministic simulation of Fernández-Villaverde and Rubio-Ramírez’ (2006) DSGE model of the U.S. economy. I calibrate the model for 2 different steady states, the first based on historical data (old steady state) and the second matching the most recent data, with lower inflation and lower real interest rates (new steady state). Within these calibrations I simulate the impact of a set of representative shocks. The ZLB appears to be of minor relevance in the old steady state while it is found to be a significant constraint in the new steady state. The associated impact on activity is relatively small but not negligible. My results are robust assuming alternative monetary policy rules. Hence, I conclude that conventional monetary policy tools are insufficient to anticipate the increased risk of hitting the ZLB in the new steady state. Further analysis of the exact transmission mechanism is warranted due to the simplified assumptions underlying this dissertation.